Tema transversal saúde nos anos iniciais da educação básica: um estudo em escolas com baixo IDEB - Santos, Marcelli Evans Telles dos (2014)
Health is one of the themes proposed by the National Curriculum Guidelines to be crafted by the school as a Transversal Theme. The Transversal Themes correspond to urgent issues for Brazilian society, expressing concepts and fundamental to democracy and citizenship and their inclusion in the school environment values implies a continuous work since the beginning of school life. In this context, this dissertation sought to identify as the health Transversal Theme was running in the early years of schools with low performance in the evaluation of the Índice de Desenvolvimento da Educação Básica (IDEB). Thus, the work was divided into three phases being developed in three public schools from Uruguaiana/RS, which had scores lower than 3.5 in IDEB 2009. The first step aimed at investigating the academic training of teacher s unidocentes in relation to themes of health and investigate aspects of the pedagogical practice of the health Transversal Theme through the application of a questionnaire to 22 teachers unidocentes. In the second stage 8 Science textbooks were analyzed to verify the presence of health and his approach as a Transversal Theme. The third step was aimed to provide educational activities for health at school and jointly identify their perceptions of health, 360 students participated in this step. According to the obtained results it can be seen, in general, that the health issue is addressed in the pedagogical practices of the schools studied, but is not handled by the teachers and the textbooks as a Transversal Theme. With regard to academic education, part of the teachers reported that they had insufficient initial training on the health issue and found that they have no prospects of continuing education. Thus, this deficit reflects in their training practices in which health issues are treated mainly in science classes, the majority of teachers, through lectures using as the main source of planning the textbook. In the second stage, the analysis showed that health occupies a few pages in the textbooks which deal mainly on diseases. The results of the third stage showed that most students associate the meaning of health eating habits and hygiene therefore, have a fragmented understanding about health. In interventions students were receptive and participative however we identified a lack of independence for carrying out the activities and considerable difficulties in working with others. Upon execution of this work gaps that need to be filled were found aiming to thus education for effective health care that can pass on a healthy life in adulthood and likewise in improving school practices in an attempt to raise the grades of respective schools on assessments of basic education. It is hoped that the questions raised in this dissertation as well as the results and inferences can cooperate in future studies on education and health in the school context and mostly generate provocations, reflections and discussions among students and professionals about school practices with Transversal Themes.